Development of Interactive Multimedia Based on Gamification Learning to Improve Learning Outcomes for Children with Disabilities - Zefanya Sherafim; I Kadek Suartama; Dewa Gede Agus Putra Prabawa (ALACRITY : Journal of Education, 2026)
This research and development aims to produce a gamification-based interactive multimedia called "Bigame" (Game Self-Development) to improve self-development learning outcomes in the Clothing and Accessories Introduction material for students with disabilities. The research was motivated by low cognitive learning outcomes due to abstract material, monotonous learning methods, and the lack of interactive media that was suitable for students' characteristics. The method used is Research and Development (R&D) with the ADDIE model including the Analysis, Design, Development, Implementation, and Evaluation stages. Data was collected through observations, interviews, questionnaires, and tests. The validity of the product is assessed by subject matter experts, learning design experts, and media experts. Practicality is tested through individual, small group tests, and teacher assessments. Effectiveness was analyzed using pre-test and post-test on 15 students with a pair sample t-test. The results showed that Bigame was systematically developed according to the ADDIE model and had "excellent" qualifications with a validity percentage of 97.14% of material experts, 97.33% of media experts, and 98% of design experts. Practicality by teachers reached 96.67% with positive student responses. The average score increased from 64.67 to 76.07 with a significance of 0.001 (<0.05) and a high effect size. It can be concluded that gamification-based interactive multimedia "Bigame" is valid, practical, and effective in improving the learning outcomes of self-development, especially clothing and accessory recognition materials, in students with disabilities.